Decarboxylative Aminomethylation of Aryl‐ and Vinylsulfonates through Combined Nickel‐ and Photoredox‐Catalyzed Cross‐Coupling. Issue 46 (10th October 2016) - Fan, Lulu; Jia, Jiaqi; Hou, Hong; Lefebvre, Quentin; Rueping, Magnus
Abstract: A mild approach for the decarboxylative aminomethylation of aryl sulfonates by the combination of photoredox and nickel catalysis through C−O bond cleavage is described for the first time. A wide range of aryl triflates as well as aryl mesylates, tosylates and alkenyl triflates afford the corresponding products in good to excellent yields. Abstract : A mild approach for the decarboxylative aminomethylation of aryl sulfonates by the combination of photoredox and nickel catalysis through C−O bond cleavage is described. A variety of aryl triflates, mesylates, tosylates, and alkenyl triflates react with α‐amino acids to afford the corresponding aminomethylated products in good to excellent yields.